Hydrological properties of oak and pine forests in Central Himalaya, India - Ravindra K Pande (Indonesian Journal of Geography, 1991)
In general, hydrological cycle in forested areas is a complicated phenomenon. In Himalaya the vegetative cover plays a vital role in determining several hydrological characters. For the experimental study of oak and pine forests hydrology, two representative basins are selected in the Central Himalaya. After evaluating the hydrological properties of oak and pine forests, it is decoded that both the vegetation types have different hydrological characteristics. However, with the destruction of vegetation and top soil, rainfall quickly runoff as stormflow instead of soaking into the soils.